Analisis Pengaruh Literasi Keuangan Syariah Terhadap Keputusan Menggunakan Produk Perbankan Syariah (Studi Mahasiswa Ekonomi Syariah Dan Perbankan Syariah Wilayah Kabupaten Bantul Yogyakarta) - Siti Aisyah; Ragil Satria Wicaksana Satria Wicaksana (AGHNIYA : Jurnal Ekonomi Islam, 2020)
Literacy is an attempt to remove all forms of public access to financial services. One of the success factors for the success of financial inclusion efforts is the level of public financial literacy. Literacy or financial literacy (financial literacy) shows the ability or level of public understanding of how money works. This study aims to determine the level of Islamic financial literacy in sharia economics and sharia banking study program students and the influence between the level of Islamic finance literacy on the use of Islamic banking products. this type of research is quantitative research. The method of data collection in this study used an online questionnaire with a sample of 134 respondents. Data analysis techniques in this study are regression tests, descriptive statistical tests, hypothesis testing (T test and F test) and coefficient of determination (). The study used SPSS 23 software and the results showed a positive influence on Islamic financial literacy on the decision to use sharia banking products with a regression coefficient of 0.746 with a significance of 0,000 with a value nilai sebesar 387. 345 0.1697can be used. The decision to use sharia banking products while the remaining 25.6% is a contribution from other factors not approved in this study.